2021
DOI: 10.1016/j.compbiolchem.2021.107463
|View full text |Cite
|
Sign up to set email alerts
|

Docking-based virtual screening studies aiming at the covalent inhibition of SARS-CoV-2 MPro by targeting the cysteine 145

Abstract: Graphical abstrcat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Ghaleb et al also studied some pyridine N -oxide compounds, indicating the most potent one with a predicted pIC 50 (the negative log of the IC 50 when converted to molar) value of 5.294. More similar works can be found in the literature. …”
Section: Methods and Approachessupporting
confidence: 56%
“…Ghaleb et al also studied some pyridine N -oxide compounds, indicating the most potent one with a predicted pIC 50 (the negative log of the IC 50 when converted to molar) value of 5.294. More similar works can be found in the literature. …”
Section: Methods and Approachessupporting
confidence: 56%
“…In subsequent simulations, we observed that these hydrogen bonds were not stable and that CCG‐50014 instead formed new hydrogen bonds and stacking interactions with the residues H41, M49, E166, and Q189. While a limited work has gone into investigating covalent inhibitors that may form disulfide bonds with the catalytic cysteine residue, 64 other studies have focused on several potential covalent inhibitors 65 , 66 , 67 , 68 , 69 , 70 , 71 which may modify the catalytic cysteine residue of M Pro via a C‐S bond. The covalent inhibitors investigated in these studies formed interactions with the residues N142, G143, H164, E166, P168, and Q189, the residues that we also observed to interact with CCG‐50014 in our work.…”
Section: Resultsmentioning
confidence: 99%
“…Undoubtedly, this is a rational strategy to predict the chances of the ligand warhead group forming a covalent adduct with its targeted nucleophilic reactive residue. A typical example of this could be found in the work of Soulère and co-workers [ 103 ]. The researchers conducted a docking-based virtual screening of covalent inhibitors with the use of the Arguslab program.…”
Section: Can Covalent Docking Be Achieved Using Conventional-docking ...mentioning
confidence: 94%